Digital Learning and Religious Moderation: An Educational Management Perspective - Moses Adeleke Adeoye; Heldy Ramadhan Putra; Hakeem Nafiu; Jamiu Tamitope Sulaimon (Universitas Sebelas Maret, 2025)
The rapid advancement of digital technologies is transforming educational paradigms worldwide. This article explores the relationship between digital learning and religious moderation from an educational management perspective, focusing on how these technologies can promote inclusivity, mitigate extremist ideologies, and enhance learning experiences. The literature review covered key concepts such as digital learning, educational management, and religious moderation, highlighting the dual-edged nature of digital technology in education. The research adopted a mixed-method approach, combining qualitative and quantitative data collection techniques. The study also found that digital learning has improved educational outcomes and personalised learning experiences, indicating high agreement between students and educators that digital learning has improved educational outcomes and personalised learning experiences. The qualitative analysis explores the themes of digital learning in religious education, focusing on access to diverse perspectives and interfaith understanding. The content analysis of digital religious education materials varies significantly, from promoting tolerance and understanding to emphasising religious distinctiveness. In conclusion, the themes revealed a dynamic yet challenging landscape for digital learning in religious education. The research suggests several recommendations, which include developing inclusive digital learning policies, promoting digital literacy skills, prioritising teacher training, and investing in high-quality digital learning materials that promote religious understanding, tolerance, and respect for diverse perspectives